Diseminasi Eksplorasi Etnomatematika pada Teknologi Tradisional di Kabupaten Kampar: Hasil PENGABMAS - Zulfah Zulfah; Astuti Astuti; Lussy Midani Rizki; Nopri Herlinda; Ika Juliana; Suci Febriani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2022)
In general, it is known that prospective mathematics teachers in Bangkinang are currently not familiar with ethnomathematical exploration in traditional technology and do not know the importance of ethnomathematical exploration and how to develop it in traditional technology. Therefore, the purpose of this study is to provide opportunities for prospective teachers in Bangkinang city regarding ethnomathematical exploration training on traditional technology for prospective teachers in Kampar Regency. This study uses the methods of planning/preparation, implementation, observation and evaluation, and reflection. The results showed that first, prospective teachers throughout Kampar Regency were enthusiastic about research ethnomathematics training to view and understand mathematics from the special cultural elements of Kampar Regency. Second, improve the knowledge and skills of prospective teachers about ethnomathematical research, especially in Kampar district and third, Ethnomathematics training materials to improve understanding of prospective teachers are attached in the appendix.